“Springboard” — a Conceptual Leap into Field of Regional Media - E. S. Radiontseva (Научный диалог)
The publication reflects on the role of the concept of publication in the conditions of the modern media market. In the conditions of the region, the project should be based on the needs and values of the target audience. The Omsk media resource Tramplin, which was born during the pandemic, is an example of a new conceptual solution. Omsk is known as a city with an “unstable” background mood, with a high migration outflow and a lack of a positive attitude towards the area of residence. In this situation, several enterprising creators decided to offer the market an alternative point of view on the space in which they live. Springboard Media is a resource about the love of the city, encouraging the reader to share this feeling. The concept of the publication resulted in a content strategy, which can be traced at the level of selection of facts, graphic and structural design of the resource. The developed content distribution system found support and response from readers. This is evidenced by the marketing audit of the resource, undertaken during the study, its results are presented in the publication. The emergence of such projects indicates a new stage in the development of regional journalism, which needs to correlate the values broadcast by the media.